Crecimiento, mortalidad y sobrevivencia de la especie Carapa guianensis “andiroba” de la plantación N° 04 del CIEFOR - Puerto Almendra, Loreto – Perú 2022 - Ortiz Davila, Romario Antonio (2023)
The objective of this study was to determine the increase in diameter and height, mortality, survival and quality of C. guianensis plants in plantation No. 4 of CIEFOR – Puerto Almendra, Iquitos. The average diameter increase was 2.8 mm in three months of evaluation. Likewise, the average increase in height of the seedlings was 8.2 cm. The plantation had a survival of 87% (174 live plants), while plant mortality was 13% (26 dead plants). The largest number of plants presented GOOD quality with 127 seedlings, representing 73% of the total. Plants with REGULAR quality reached 39 individuals representing 22.4%: plants with BAD quality presented 8 seedlings, representing 4.6% of the total. As for the analysis of variance, it was determined that there is a significant difference between the strips and the average increase in diameter, however there is no difference in the average increase in height. It is necessary to continue with the biometric evaluations of the plantation and to carry out similar studies with other promising forest species at CIEFOR - Puerto Almendra.